PENELITIAN PERUBAHAN WARNA DAN ETILEN SELAMA PEMERAMAN DAUN TEMBAKAU KULTIVAR MADURA SERTA PENGARUHNYA TERHADAP MUTU TEMBAKAU RAJANGAN - JOKO PURDIYANTO (Jurnal Penelitian Tanaman Industri, 2001)
Colour alternation and et/tylene changes during ripening tobacco leaves cultivar Madura and its effect to the quality of slice Madura tobaccoThe colour change and elhylene production in the leaves of Madura tobacco (Nicotiana tabacum) during ripening was studied at "Labora¬ torium Biokimia Pusat Antar Universitas Pangan dan Gizi Universitas Gadjahmada Yogyakata" and "Laboratorium Inti dan Atom Jurusan I'isika, FMIPA Universitas Gadjahmada Yogyakata". The change of colour was measured with Chrommameter CR-200. while the production of ethylcne, ACC (1-aminocyclopropanc-l-carboxylic acid) and MACC (malonyl-ACC) were measured with Photoaccuslic Spectroscopy, from the sample of 100 kg tobacco leaves cv. Jepon grown from April to September 1995 in Plakpak, Pcgantenan, Pamekasan, East Java. The experiment was designed as a completely randomized design in three replicates. The leaves samples were taken randomly from the mature middle leaves Results showed that endogenous ethylcne production al the irst day al a level of 169 ppb. was able to initiate ripening. Conversion percentage of ACC to ethylcne for 8 days ripening increased from 7.7 up lo 61.4 %. F tests least signiicantly different (1%). showed that yellow intensity signiicantly increased on the second day. This indicated thai ripening process was stated on the second day. On the other hand green intensity significantly decreased at the ifth day, thus no chlorophyl degradation. Brightness was signiicantly observed on Ihe third day of ripening, meaning that ripening stated on the third day. Based on the three criteria, the best ripening period was from the third lo the ilth day. This implies that the farmers will have three day periods of ripening which can be arranged to overcome the shotage of man power for slicing the leaves.